2019
DOI: 10.1159/000502418
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine Dosage as Predictor of Permanent and Transient Congenital Hypothyroidism: A Multicenter Retrospective Study in Japan

Abstract: <b><i>Background:</i></b> Congenital hypothyroidism (CH) can be divided into 2 types, transient CH (T-CH) and permanent CH (P-CH), depending on the requirement of levothyroxine (LT4) for life-long treatment. Several studies have recently reported that the LT4 dosage is useful for predicting the LT4 requirement, but none of the studies followed their patients to puberty. <b><i>Objective:</i></b> To determine the cutoff value for the LT4 dosage as a predictor of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…We also detected the mean of L-T 4 dosages at the age of 3 yr were 3.9 µg/kg/d and 2.2 µg/kg/d in group P and group T, respectively. These were similar to the cutoff values in previous foreign studies ( 6 , 9 ), and on the other hand slightly higher than the cutoff of T-CH in Japanese patients ( 11 , 12 ). This difference may be caused by the relatively small sample size and lack of data, especially body weight, in some patients in our study.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We also detected the mean of L-T 4 dosages at the age of 3 yr were 3.9 µg/kg/d and 2.2 µg/kg/d in group P and group T, respectively. These were similar to the cutoff values in previous foreign studies ( 6 , 9 ), and on the other hand slightly higher than the cutoff of T-CH in Japanese patients ( 11 , 12 ). This difference may be caused by the relatively small sample size and lack of data, especially body weight, in some patients in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have also demonstrated the cutoff of L-T 4 dosages with P-CH and T-CH ( 6 , 9 , 11 , 12 ). In Japanese patients, Higuchi et al showed the cutoff of L-T 4 dosages suspicious of T-CH as 2.4 µg/kg/d at the age of 1 yr and 1.3 µg/kg/d at the age of 3 yr ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations